HUBUNGAN STADIUM CHRONIC KIDNEY DISEASE DENGAN HIPERTENSI PADA PASIEN CKD DEWASA DI RSUP DR. M. DJAMIL PADANG TAHUN 2020-2021. - Putri, Viona Salsabila; Miro, Saptino; Irawati, Lili; Fadrian, Fadrian; Hamdani, Rita; Rasyid, Rosfita (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Chronic Kidney Disease (CKD) is a condition where there is structural or functional damage to the kidneys for more than 3 months with or without being followed by a decrease in the estimated Glomerular Filtration Rate (eGFR) and is progressive and irreversible. Hypertension is the most common comorbidity found in patients with CKD which can increase the progression of kidney damage. Objective: To determine the relationship between the stage of CKD and hypertension and the distribution of the frequency of patients with CKD based on age, sex, eGFR value, and hypertension. Methods: This research was an observational analytic study with a cross-sectional design. The research was conducted at the Medical Record Installation of RSUP Dr. M. Djamil from December 2022 - March 2023 used a purposive sampling technique and obtained 33 samples. The research data was secondary data in the form of blood pressure and serum creatinine and then analyzed using the Chi-Square test with a degree of confidence of 95% and p-value <0,05. Results: This study showed that most cases of CKD occurred in the age group 41-65 years (54,5%) and mostly found in men (57,6%). In this study, stage 5 CKD was the most common (72,7%) and the majority of patients with CKD suffered from hypertension (69,7%). The results of data analysis obtained p = 0,090 (p> 0.05). Conclusion: There was no significant relationship between the stage of CKD and hypertension (P=0,090) in adult patients at Dr. M. Djamil Padang in 2020–2021.